The study of the influence of Thlaspi arvense L. on the characteristics of the reproductive system of male rats - R. G. Farkhutdinov; K. A. Pupykina; L. A. Sharafutdinova; A. M. Fedorova; Z. R. Hismatullina; M. I. Garipova; E. F. Koroleva; A. A. Yamaleeva; T. D. Rendyuk (Разработка и регистрация лекарственных средств, 2024)
Introduction. The development of new effective and safe herbal medicines capable of having a positive effect on reproductive status is an urgent task of domestic pharmacy. Medicinal plants are considered as alternative therapies aimed at increasing testosterone levels and fertility in men. The arsenal of medicinal plants used in traditional medicine for the treatment of diseases in men is mainly represented by phytoadaptogens, most of which have a small resource potential in Russia, therefore, it is relevant to search for plants with a sufficient raw material base and with the potential for cultivation. Thlaspi arvense L. is a promising medicinal plant, as it is widely used in folk medicine as a diuretic, anti-inflammatory, diaphoretic, antihistamine, hemostatic, astringent, has a positive effect on the processes of spermatogenesis and is widely distributed in our country. However, information on the chemical composition and biological activity of Thlaspi arvense L. they are insufficient, which shows the relevance of its further more detailed study in order to substantiate the possibility of application in practical medicine and solutions to the issues of standardization of medicinal plant raw materials.Aim. The study of the influence of Thlaspi arvense L. on the characteristics of the reproductive system of male rats.Materials and methods. The object of the study was an infusion of herbа Thlaspi arvense L. The features of the reproductive behavior of male rats after 21-day administration of the infusion of grass yarutka field were studied using tests that allow quantifying the severity of sexual motivation and sexual activity of males. The viability of spermatozoa in the ejaculate of rats was assessed, the total number of spermatozoa (ACS, million), degenerative and immobile forms (%) was calculated. Morphophysiological parameters of spermatogenesis of rats of control and experimental groups of animals were studied using classical histological methods. The concentration of testosterone in the blood serum of experimental groups of animals was determined by the enzyme immunoassay.Results and discussion. The results obtained allow us to conclude that the fertility of rats has increased against the background of the course administration of the infusion of herbа Thlaspi arvense L., as evidenced by an increase in the testosterone content in the blood, improvement of spermogram indicators and morphophysiological characteristics of spermatogenesis in the testicles of rats. The use of the infusion of herbа Thlaspi arvense L. has a protective effect on spermatogenesis. An increase in the thickness of the spermatogenic epithelium, the diameter of the cross-section of the convoluted seminal tubules and the index of spermatogenesis compared with the control group of animals was revealed. The positive effect of Thlaspi arvense L. on indicators of sexual motivation and sexual activity of male rats is shown.Conclusion. Thlaspi arvense L. is a promising medicinal plant, as it is able to have a positive effect on libido, the number and mobility of spermatozoa, the production of sex hormones, spermatogenesis, as well as on the pituitary-gonadal axis, which is associated with the content of a complex of biologically active substances in it.